Manusia dan Kehancurannya: Sebuah Tinjauan Reflektif atas Filsafat Jean Paul Sartre - Mamput, Yulianus Gunawan (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
This paper explores the relationship between humanity and violence. Violence is often the result of a failure to promote empathy and solidarity. This is exemplified by the Holocaust and the New Order regime in Indonesia. The paper highlights the complex nature of human emancipation and emphasizes the importance of considering the well-being of others as well as one's own self. The concept of emancipation is evident in the philosophies of notable figures including Descartes, Kant, Marx, and Comte. Sartre, too, advocated for humanist freedom, but conceded that unlimited freedom can lead to egoism. This paper will center on the ideas of Jean-Paul Sartre, ultimately concluding that the destruction of humanity can be traced back to anthropological and social aspects of society.AbstrakTulisan ini mengeksplorasi hubungan antara kemanusiaan dan kekerasan. Kekerasan sering kali merupakan hasil dari kegagalan untuk mempromosikan empati dan solidaritas. Hal ini terepresentasi oleh peristiwa Holocaust dan rezim Orde Baru di Indonesia. Makalah ini menyoroti kompleksitas  emansipasi manusia dan menekankan pentingnya mempertimbangkan kesejahteraan orang lain dan juga diri sendiri. Dilema emansipasi terlihat jelas dalam para pemikir terkenal seperti Descartes, Kant, Marx, dan Comte. Sartre juga menganjurkan kebebasan humanis, tetapi mengakui bahwa kebebasan yang tidak terbatas dapat mengarah pada egoisme. Tulisan ini akan berpusat pada ide-ide Jean-Paul Sartre, yang pada akhirnya menyimpulkan bahwa kehancuran umat manusia dapat ditelusuri kembali ke aspek antropologis dan sosial masyarakat.